KEANEKARAGAMAN KARANG KERAS DAN IKAN TERUMBU DI PANTAI PAPUMA JEMBER, JAWA TIMUR - LUTHFI, OKTIYAS MUZAKY; WIBISONO, RENDY VIDYA (Jurnal Biologi Udayana; Vol 22 No 1 (2018): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2018.v22.i01.p03, 2018)
ABSTRACT   Coral reef in Papuma was distributed in 3 to 20 m depth, with sand as main substrate. The coral reef was built from hard coral (scleractinian) and reef fishes. Papuma’s coral reef was interesting to be studied due to they can deal with the extreme environment such as high sand sedimentation, high wave, strong current, and anthropogenic risk. The purpose of this study was to descript distribution of hard coral and their fishes based on quantitative data in Papuma. We used Line Intercept Transect (LIT) method with 100 m long perpendicular with coast line to quantify of coral cover based on their life form. While reef fishes data was obtained using underwater visual census with 100 m long. All data was taken from 3 stasiun they were: station 1 (8°25'59.26"S 113°33'15.07"E), station 2 (8°26'0.93"S 113°33'17.53"E) and station 3 (8°26'2.02"S 113°33'20.06"E), in 3-12 m depth.  The result showed that coral reef in Papuma was dominated by branching coral (CB) from genus Montipora with coral cover 30%, while sand (SD) to be main substrate with 26.9% of coverage.  Montipora is one of genus famili Acroporidae that has faster growth than massive coral and strong branch as an adaptation strategy with strong current. In this research, we also found 137 of reef fishes that was 19% composed by indicator fish (Chaetodontidae). High number of indicator fish can represent of healthy coral reef. High coral cover coverage usually will be followed by increasing number of indicator fish. These fish were obligate corallivorous that consume coral polyp during their life. Coral reef in Papuma contained 10 types of life form and had coral cover about 39.9% in average.